A Polynomial Linear Search Algorithm forr the n-Dimensional Knapsack Problem - Meyer auf der Heide, Friedhelm (Journal of the ACM (JACM))

On The Limits To Speed Up Parallel Machines By Large Hardware And Unbounded Communication - Meyer auf der Heide, Friedhelm; Reischuk, R. (25th Annual Symposium onFoundations of Computer Science, 1984.)

Efficient simulations among several models of parallel computers (extended abstract) - Meyer auf der Heide, Friedhelm (STACS 84)

Method to Relate Digital SAR Images and Map Information in Mountainous Areas - Domik, Gitta; Kienegger, E. (Proceedings of the World Conference on Remote Sensing)

The SAR-580 experiment on snow and glaciers at the Austrian test site - Rott, H.; Domik, Gitta (Proc. SAR-580 Investigators Workshop)

Differential Rectification of SLR-Images Using Map-Derived and Radar-Generated Digital Elevation Models. - Domik, Gitta; Leberl, Franz; Raggam, Johannes

Analyse von Radarbildern mittels digitaler Hoehenmodelle - Domik, Gitta; Kobrick, M; Leberl, Franz (Bildmessung und luftbildwesen)

Der nationalsozialistische „neue Begriff“ von Wissenschaft am Beispiel der „Deutschen Mathematik“ — Programm, Konzeption und politische Realisierung, Magisterarbeit an der Philosophischen Fakultät der Rheinisch-Westfälischen Technischen Hochschule Aachen, August 1984 - Peckhaus, Volker
Online-Version (2001, 2014): http://publications.rwth-aachen.de/record/229987

Das Schöne Als Vollzug Der Liebe. Eros-Logos-Verhältnisse in Platons Symposion - Hagengruber, Ruth Edith

Lie Theory of Semigroups - Hilgert, Joachim; Hofmann, K.H. (Semigroup Forum)

Radar image simulation as a tool to analyze topographic effects on geometry and radiometry of radar imagery - Domik, Gitta (Machine processing of remotely sensed data- Quantifying global process: Models, sensor systems, and analytical methods)

Radargrammetric aspects of SAR data evaluation - Raggam, J; Triebnig, Gerhard; Buchroithner, MF; Domik, Gitta; Leberl, Franz (Thematic Applications of SAR data)

Graph Grammar Engineering: A Method Used for the Development of an Integrated Programming Support Environment - Engels, Gregor; Schäfer, Wilhelm (Proceedings of the International Joint Conference on Theory and Practice of Software Development (TAPSOFT 1985), Berlin (Germany))
We introduce a method to specify the functional behaviour of software tools in an incremental and integrated software development environment. This specification method is based on graph grammars. It is an adequate method to specify the behaviour of all software systems using graphs as internal data structures. We show that a specification can be developed systematically by which the adaptability of the environment is increased towards modification of tools or extension by new tools. Furthermore, guidelines for the implementation can directly be derived from this specification.

The Design of an Adaptive and Portable Programming Support Environment - Engels, Gregor; Schäfer, Wilhelm (Proceedings of the International Computing Symposium, Amsterdam (The Netherlands))

Lower time bounds for integer programming with two variables - Lautemann, Clemens; Meyer auf der Heide, Friedhelm (Information Processing Letters)

Lower bounds for solving linear diophantine equations on random access machines - Meyer auf der Heide, Friedhelm (Journal of the ACM (JACM))

Simulating probabilistic by deterministic algebraic computation trees - Meyer auf der Heide, Friedhelm (Theoretical Computer Science)

The complexity of parallel sorting - Meyer auf der Heide, Friedhelm; Wigderson, Avi (26th Annual Symposium on Foundations of Computer Science (sfcs 1985))

One, two, three . . . infinity: lower bounds for parallel computation - Fich, F E; Meyer auf der Heide, Friedhelm; Ragde, P; Wigderson, A (Proceedings of the seventeenth annual ACM symposium on Theory of computing - STOC '85)

Fast algorithms for n-dimensional restrictions of hard problems - Meyer auf der Heide, Friedhelm (Proceedings of the seventeenth annual ACM symposium on Theory of computing - STOC '85)

Nondeterministic versus probabilistic linear search algorithms - Meyer auf der Heide, Friedhelm (26th Annual Symposium on Foundations of Computer Science (sfcs 1985))

Lower time bounds for solving linear diophantine equations on several parallel computational models - Meyer auf der Heide, Friedhelm (Information and Control)

Mapping with aircraft and satellite radar images - Leberl, FW; Kobrick, M; Domik, Gitta (The Photogrammetric Record)

Towards a SAR system for snow and land ice applications - Rott, H; Domik, Gitta; Mätzler, C; Miller, H (ESA Proceedings of a Workshop on Thematic Applications of SAR DATA p 29-39(SEE N 86-28488 19-42))

Distribution of Correlation Times in Glassy Polymers From Pulsed Deuteron NMR - Schmidt, Claudia; Kuhn, Karl J.; Spiess, Hans W. (Progress in Colloid and Polymer Science)

ELECTROOPTICAL BEHAVIOR OF CHOLESTERIC BLUE PHASES WITH NEGATIVE DIELECTRIC ANISOTROPY - HEPPKE, G; Kitzerow, Heinz-Siegfried; KRUMREY, M (MOLECULAR CRYSTALS AND LIQUID CRYSTALS)

ELECTRIC-FIELD INDUCED VARIATION OF THE REFRACTIVE-INDEX IN CHOLESTERIC BLUE PHASES - HEPPKE, G; Kitzerow, Heinz-Siegfried; KRUMREY, M (MOLECULAR CRYSTALS AND LIQUID CRYSTALS)

Controllabilty of Systems on Nilpotent Lie Groups - Hilgert, Joachim; Hofmann, K.H.; Lawson, J.D. (Beiträge Alg. Geom.)

Semigroups in Lie Groups, Semialgebras in Lie Algebras - Hilgert, Joachim; Hofmann, K.H. (Trans. AMS)

Lorentzian Cones in Real Lie Algebras - Hilgert, Joachim; Hofmann, K.H. (Monatshefte Math.)

Lie Semialgebras are Real Phenomena - Hilgert, Joachim; Hofmann, K.H. (Math. Ann.)

Old and New on SL(2) - Hilgert, Joachim; Hofmann, K.H. (Manuscripta Math.)

Architekten- und Künstlerbiographien - Seng, Eva- Maria (Ehrwürdige Zeugen verschwundener Tage, Tübinger Baudenkmale in Architekturzeichnungen des 19. Jahrhunderts, Katalog zur Ausstellung Tübingen 1986 (Tübinger Kataloge Nr. 29))

Classes of first order formulas under various satisfiability definitions - Kleine Büning, H.; Lettmann, Theodor (8th International Conference on Automated Deduction)

Die Zeichner und die Art der Darstellung - Zur Entwicklung und Funktion der Architekturzeichnung im 19. Jahrhundert - Seng, Eva- Maria (Ehrwürdige Zeugen verschwundener Tage, Tübinger Baudenkmale in Architekturzeichnungen des 19. Jahrhunderts, Katalog zur Ausstellung Tübingen 1986 (Tübinger Kataloge Nr. 29))

Das Ulmer Hauptwerk: Der Blaubeurer Hochaltar und die Erhart-Frage - Seng, Eva- Maria (Blätter für württembergische Kirchengeschichte, 86. Jg.)

Risse: Pytheas, Philostratos et. al. Zu den Protagonisten der frühen Erzählungen Arno Schmidts - Eke, Norbert Otto (Arno Schmidt. Das Frühwerk I: Erzählungen. Interpretationen von ‚Gadir‘ bis ‚Kosmas‘)

Belgium in a Nutshell Investitionsmöglichkeiten ausländischer Unternehmen in Belgien - Krimphove, Dieter

Multiple incidence angle SIR-B experiment over Argentina: generation of secondary image products - Domik, Gitta; Leberl, Franz; Cimino, Jobea (IEEE Transactions on Geoscience and Remote Sensing)

Digital terrain mapping with STAR-1 SAR data - Mercer, JB; Lowry, RT; Leberl, Franz; Domik, Gitta (International Geoscience and Remote Sensing Symposium)

Developing tools for digital radar image data evaluation - Domik, Gitta; Leberl, Franz; Raggam, J (Remote sensing for resources development and environmental management; Proceedings of the Seventh International Symposium)

On the Structure of an Incremental and Integrated Software Development Environment - Engels, Gregor; Lewerentz, Claus; Nagl, Manfred; Schäfer, Wilhelm (Proceedings of the 19th Hawaii International Conference on System Sciences, Hawaii, USA)

Experiences with a Hybrid-Interpreter Based on Incremental Compilation Techniques - Engels, Gregor; Sandbrink, Andrea (Proceedings of the Workshop on Compiler Compilers and Incremental Compilation Techniques, Bautzen)

Graphen als zentrale Datenstrukturen in einer Software-Entwicklungsumgebung - Engels, Gregor

Efficient Simulations among Several Models of Parallel Computers - Meyer auf der Heide, Friedhelm (SIAM Journal on Computing)

A tradeoff between search and update time for the implicit dictionary problem - Borodin, Allan; Fich, Faith E.; Meyer auf der Heide, Friedhelm; Upfal, Eli; Wigderson, Avi (Automata, Languages and Programming)

Speeding up random access machines by few processors - Meyer auf der Heide, Friedhelm (STACS 86)

A time-space tradeoff for element distinctness - Borodin, A.; Fich, F.; Meyer auf der Heide, Friedhelm; Upfal, E.; Wigderson, A. (STACS 86)

Radar Stereomapping Techniques and Application to SIR-B Images of Mt. Shasta - Leberl, F.; Domik, Gitta; Raggam, J.; Kobrick, M. (IEEE Transactions on Geoscience and Remote Sensing)

Multiple Incidence Angle SIR-B Expenment Over Argentina: Stereo-Radargrammetrc Analysis - Leberl, F.; Domik, Gitta; Raggam, J.; Cimino, J.; Kobrick, M. (IEEE Transactions on Geoscience and Remote Sensing)

An all digital implementation of a receiver for bandwidth-efficient communication - Oerder, Martin; Ascheid, Gerd; Haeb-Umbach, Reinhold; Meyr, Heinrich (Signal Processing: Theories and Applications)

Deformation dicker Punkte und Netze von Quadriken - Hellebrand, Sybille

Using secondary image products to aid in understanding and interpretation of radar imagery - Domik, Gitta; Leberl, Franz (IGARSS'86: Remote Sensing: Today's Solutions for Tomorrow's Information Needs)

Radargrammetric Experiments with Space Shuttle SIR-B Imagery - Leberl, Franz; Domik, Gitta; Raggam, J; Cimino, J; Kobrick, M (International archives of photogrammetry and remote sensing= Archives internationales de photogrammétrie et de télédétection= Internationales Archiv der Photogrammetrie und Fernerkundung)

Case Studies Towards the Establishment of a Social History of Logic - Peckhaus, Volker (History and Philosophy of Logic)
Abstracts: Historia Mathematica 18 (1991), 400 (#18.4.67); Historical Abstracts 39A:4291.

Nichtlineare und adaptive Regelungssysteme - Böcker, Joachim; Hartmann, Irmfried; Zwanzig, Christian

Dynamics of molecular reorientations: direct determination of rotational angles from two-dimensional NMR of powders - Schmidt, Claudia; Wefing, S.; Blümich, B.; Spiess, H.W. (Chemical Physics Letters)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Eine empirische Untersuchung zu den schriftsprachlichen Leistungen türkischer Schulkinder - Beckemeyer, Rita; Tophinke, Doris (Narrative Kompetenz. Mündliche und schriftliche Wiedergabe von Erzählstrukturen durch türkische Schulkinder in außerschulischen Lerngruppen)

Geschlechtsspezifische Arbeitsteilung und technische Innovation - Neue Technologien, Frauenerwerbsarbeit und historisch-genetisches Lernen über Arbeit und Technik. - Bigga, Regine; Oberliesen, R. (Neue Technologien und technisch-ökonomische Bildung.)

ENDLESS POLARIZATION CONTROL EXPERIMENT WITH 3 ELEMENTS OF LIMITED BIREFRINGENCE RANGE - Noé, Reinhold (ELECTRONICS LETTERS)

ENDLESS POLARIZATION CONTROL IN COHERENT OPTICAL COMMUNICATIONS - Noé, Reinhold (ELECTRONICS LETTERS)

Optisches System mit einer Flüssigkristallzelle, Verfahren zu seinem Betrieb und seine Verwendung - Heppke, G.; Oestreicher, F.; Kitzerow, Heinz-Siegfried; Krumrey, M.

Das Städtische Orchester 1921–1955 - Grotjahn, Rebecca (Das Niedersächsische Staatsorchester 1636–1986)

Invariant Cones in Real Lie Algebras - Hilgert, Joachim; Hofmann, K.H. (Aspects of Positivity in Functional Analysis)

The Mayer-Vietoris and the Puppe Sequence in K-Theory for C*-algebras - Hilgert, Joachim (Studia Math.)

On the Automorphism Group of Cones and Wedges - Hilgert, Joachim; Hofmann, K.H. (Geom. Dedicata)

On Sophus Lie's Fundamental Theorem - Hilgert, Joachim; Hofmann, K.H. (J. Funct. Anal.)

Representation independent query and update operations on propositional definite Horn formulas - Büning, Hans Kleine; Lettmann, Theodor (Computation Theory and Logic)

DFG fördert an der FAU: Projekt: Fallstudien zur Begründung einer Sozialgeschichte der Logik - Peckhaus, Volker; Thiel, Christian (FAU Uni-Kurier)

Ein Hauch von Paris ... Die Planung für den Tübinger Uhlandplatz durch Christian Friedrich von Leins - Seng, Eva- Maria (Tübinger Blätter, 74. Jg.)

Image based SAR product simulation for analysis - Domik, Gitta; Leberl, Franz (ASPRS-ACSM)

A Hybrid Interpreter in a Software Development Environment - Engels, Gregor; Schürr, Andy (Proceedings of the 1st European Software Engineering Conference (ESEC '87), Strasbourg (France))
This paper describes the realization of an execution tool for Modula-2 modules which is part of an integrated tool set in a software development environment termed IPSEN (Incremental Programming Support Environment). In this environment, all software documents, e.g. Modula-2 modules, are manipulated by syntax-directed editors and are represented internally by attributed graphs. The execution of Modula-2 modules is done by two cooperating interpreters. The first one is a graph interpreter which traverses the internal graph from statement to statement. These statements are translated into a low-level, more efficiently executable object code and interpreted by a second interpreter. This concept of a hybrid interpreter allows the realization of an execution tool which offers a lot of runtime support features to the user.

On the Structure of Structure-Oriented Editors for Different Applications - Engels, Gregor; Nagl, Manfred; Schäfer, Wilhelm (Proceedings of the ACM SIGSOFT/SIGPLAN Software Engineering Symposium on Practical Software Development Environments, Palo Alto, USA)

Graph Grammar Engineering: A Software Specification Method - Engels, Gregor; Lewerentz, Claus; Schäfer, Wilhelm (Proceedings of the 3rd International Workshop on Graph-Grammars and Their Application to Computer Science, Warrenton, VA (USA))
Graphs as conceptual data models are accepted and used in a wide range of different problem areas. Giving some examples we outline common aspects for modeling complex structures by graphs. We present a formal frame-work based on graph grammars to specify graph classes and the corresponding graph manipulations. We show that such a specification can be written in a systematic, engineering-like manner. This is achieved by an extension of the known programmed, attributed graph grammars. Node-set operators are introduced to facilitate graph queries. Concepts like abstraction, decomposition, refinement, parameterization, and integration have been adopted from software engineering to yield a comprehensive specification method. This method has successfully been applied to specify the central data structures in a software development environment project

A Time-Space Tradeoff for Element Distinctness - Borodin, A.; Fich, F.; Meyer auf der Heide, Friedhelm; Upfal, E.; Wigderson, A. (SIAM Journal on Computing)

The Complexity of Parallel Sorting - Meyer auf der Heide, Friedhelm; Wigderson, Avi (SIAM Journal on Computing)

Digital Rectification Method for Radar Images Applied on Huge Arrays - Domik, Gitta (Proceedings of the First Int'l. Workshop on Image Rectification Tech. for Spaceborne Synthetic Aperture Radar)

Optimal Carrier Recovery and Detection on Frequency-Nonselective Fading Channels - Haeb-Umbach, Reinhold; Meyr, Heinrich (Proc. Symposium on Inf. Theory and Appl. (SITA), Tokio)

Methods and application of surface shape reconstruction from multiple SAR images - Domik, Gitta (IGARSS'87-International Geoscience and Remote Sensing Symposium)

Methods and accuracy of operational digital image mapping with aircraft SAR - Leberl, Franz; Domik, Gitta; Mercer, Bryan J (1987 ASPRS ACSM Annual Convention)

Interdisziplinäres Institut für Wissenschaftstheorie und Wissenschaftsgeschichte - Peckhaus, Volker; Kötter, Rudolf (Friedrich-Alexander-Universität Erlangen-Nürnberg. Jahresbericht 1984/85 und 1985/86 (Mai 1987))

Molecular motions from two-dimensional NMR of powders: Comparison of rotational jumps and diffusive reorientations - Schmidt, Claudia; Blümich, B.; Wefing, S.; Kaufmann, S.; Spiess, H. W. (Berichte der Bunsengesellschaft für physikalische Chemie)
Keywords: General Chemical Engineering

Anschauliches Lernen im Museum. - Bigga, Regine (Allgemeinbildung und Arbeit, Technik, Wirtschaft - Innovationen in Curriculum und Schul-Praxis.)

Ruth Crawford Seeger - Grotjahn, Rebecca (Amerikanische Musik seit Charles Ives)

Wallingford Riegger - Grotjahn, Rebecca (Amerikanische Musik seit Charles Ives)

George Rochberg - Grotjahn, Rebecca (Amerikanische Musik seit Charles Ives)

Angular Dependence of Blue Phase Selective Reflection in the Electric Field - Heppke, G.; Kitzerow, Heinz-Siegfried; Krumrey, M. (Molecular Crystals and Liquid Crystals Incorporating Nonlinear Optics)
Keywords: General Medicine

Theoretische und numerische Aspekte der Berechnung thermo-mechanischer Kriechvorgänge im Steinsalz - Mahnken, Rolf; Stein, Erwin; Wetjen, Diedrich; Heemann, Ulrich (Abhandlungen der Braunschweigischen Wissenschaftlichen Gesellschaft)

Maximal Semigroups and the Support of Gauss-Semigroups - Hilgert, Joachim (Probability and Baysian Statistics)

Maximal Semigroups and Controllability in Products of Lie Groups - Hilgert, Joachim (Archiv Math.)

Kapitel 3: Das Genehmigungsverfahren der Studie an Patienten mit „Angstzuständen“ unter Mitarbeit von Florina Steger, Jan Jeskow) - Hartig, Christine (Das Antidepressivum Levoprotilin in Jena. Arzneimittelstudien westlicher Pharmaunternehmen in der DDR)

Perspektiven für die Logikprogrammierung - Kleine Büning, Hans; Lettmann, Theodor (Workshop Wissensrepräsentation in Expertensystemen)

Historiographie wissenschaftlicher Disziplinen als Kombination von Problem- und Sozialgeschichtsschreibung: Formale Logik im Deutschland des ausgehenden 19. Jahrhunderts - Peckhaus, Volker (Die geschichtliche Perspektive in den Disziplinen der Wissenschaftsforschung. Kolloquium an der TU Berlin, Oktober 1988. Mit Beiträgen von Michael Heidelberger, Walter Kaiser, C. Ulises Moulines, Volker Peckhaus, Wolf Schäfer, Burghard Weiss)

Die Johanneskirche am Feuersee in Stuttgart und der Architekt Christian Friedrich von Leins (1814 - 1892), Magisterarbeit masch. - Seng, Eva- Maria

„Wenn man die Augen hätte schließen und schlafen können...“. Zu Arno Schmidts Nachkriegsroman „Brand’s Haide“ - Eke, Norbert Otto (Arno Schmidt. Das Frühwerk II. Romane. Interpretationen von ‚Brand’s Haide’ bis ‚Gelehrtenrepublik’)

A Highly Integrated Tool Set for Program Development Support - Engels, Gregor; Janning, Thorsten; Schäfer, Wilhelm (Proceedings of the conference on ACM SIGSMALL/PC symposium on ACTES (SIGSMALL 1988), Cannes (France))
This paper describes the design of the integrated user interface of the software development environment IPSEN (Integrated Programming Support Environment). We explain the characteristic features of the IPSEN user interface, namely the structured layout of the screen, the command-driven tool activation, and especially the highly integrated use of the IPSEN tool set. We demonstrate those features by taking a sample set of tools of the IPSEN environment. That tool set supports all the programming-in-the-small activities within IPSEN. Finally, we sketch the realization of two prototypes running on an IBM-AT and a net of SUN workstations.

Konzeption einer integrierten Datenbank-Entwurfsumgebung - Engels, Gregor; Hohenstein, Uwe; Neugebauer, Leonore; Saake, Gunter; Ehrich, Hans-Dietrich (Proceedings of DBTA/SI Data Dictionaries und Entwicklungswerkzeuge für Datenbank-Anwendungen, Zürich, Switzerland)

Auf dem Weg zu einer integrierten Datenbank-Entwurfsumgebung - Engels, Gregor; Hohenstein, Uwe; Saake, Gunter; Ehrich, Hans-Dietrich (Proceedings of the GI-Workshop on "Sprachspezifische Programmierumgebungen")

Ein Konzept zur Beschreibung von Software-Architekturen - Ebert, Jürgen; Engels, Gregor

Die Benutzerschnittstelle einer integrierten Modula-2 Programmentwicklungsumgebung - Engels, Gregor; Janning, Thorsten; Schäfer, Wilhelm (Proceedings of GI-Workshop Sprachspezifische Programmierumgebungen, Darmstadt, Germany)